Chapter POLICRYPS Composite Materials: Features and Applications - De Sio, L.; Veltri, Alessandro; Tabiryan, Nelson V.; Caputo, Roberto; Sukhov, A. V.; Umeton, C. (InTechOpen, 2011)
Physical chemistry
English
Keywords: Electrochemistry & magnetochemistry; Mathematics & science